A Note on the Tracing of Herbage Contribution to Grazing Sheep Diet Using Milk and Feces Biomarkers - Molle, Giovanni; Cabiddu, Andrea; Decandia, Mauro; Acciaro, Marco; Scanu, Giuseppe; Addis, Margherita; Fiori, Myriam; Caredda, Marco (Frontiers in Veterinary Science, 2021)
Milk from grazing ruminants is usually rich in beneficial components for human health but distinguishing milks sourced from grazing is difficult and this hinders the valuing of this grazing benefit. This study aimed at evaluating the ability of milk biomarkers 1) to trace milks sourced from sheep submitted to different access time (AT) to pasture; and 2) to estimate sheep herbage intake (HDMI, g DM ewe-1 d-1) and herbage percentage in sheep diet (HP, % DM). Animal data derives from a published experiment in which six replicated groups of mid lactation Sarda sheep had AT of 2, 4 or 6 h d-1 on a ryegrass pasture. Sheep HDMI and HP of each group were measured on four dates in April 2013. Group milk was sampled and milk fatty acids (FA) and n-alkanes determined by gas-chromatography. The latter markers were also measured in feces samples bulked by group. The data (N = 24 records) were submitted to linear discriminant analysis (LDA) aimed at distinguishing the AT to pasture based on biomarkers previously selected by Genetic Algorithms (GA). Partial least square regression (PLSR) models were used to estimate HDMI and HP using biomarkers selected by GA. The GA-LDA showed high accuracy, with 95.8% of correct estimates using one milk alkane and six milk FA as biomarkers. The estimation of HDMI by GA-PLSR based on five milk FA was moderately precise (explained variance = 75.2%; percentage of the residual mean square error of cross validation over the mean value (RMSECV%) = 15.0%). The estimation of HP by GA-PLSR based on one milk alkane and ten FA was precise (explained variance = 80.8%; RMSECV% = 7.4%). To conclude, these preliminary results suggest that milks sourced from sheep flocks with AT to pasture differentiated by 2 h in the range 2-6 h d-1 can be precisely discriminated using milk biomarkers. The contribution of herbage to sheep diet can also be precisely estimated.